Nitric oxide (NO)-mediated mitochondrial damage plays a critical role in T-2 toxin-induced apoptosis and growth hormone deficiency in rat anterior pituitary GH3 cells. (April 2017) - Liu, Xianglian; Guo, Pu; Liu, Aimei; Wu, Qinghua; Xue, Xijuan; Dai, Menghong; Hao, Haihong; Qu, Wei; Xie, Shuyu; Wang, Xu; Yuan, Zonghui
Abstract: T-2 toxin, a major compound of trichothecenes, induces cell apoptosis and growth hormone (GH) deficiency and causes considerable growth retardation in animals and human cells. However, the mechanism underlying its growth suppression still remains unclear. Recent studies have suggested that ROS induced cell apoptosis and animal feed intake reduction, but there are limited reports on the role of RNS in T-2 toxin-mediated mitochondrial damage, cell apoptosis and growth retardation. Herein, T-2 toxin-induced GH3 cell damage and apoptosis were tested by MTT assay, LDH leakage and flow cytometry, respectively. Intracellular NO and antioxidant enzyme activity, ΔΨm, morphometric changes of mitochondria, the caspase pathway, and inflammatory factors were investigated. Free radical scavengers NAC, SOD and NO scavenger haemoglobin were used to explore the role of oxidative stress and the relationship between NO production and caspase pathway. The results clearly revealed that T-2 toxin caused significant increases in NO generation, cell apoptosis, GH deficiency, increased iNOS activity, upregulation of inflammatory factors and caspase pathway, decreases in ΔΨm and morphosis damage. These data suggest that mitochondria are a primary target of T-2 toxin-induced NO, and NO is a key mediator of T-2 toxin-induced cell apoptosis and GH deficiency via the mitochondria-dependent pathway in cells. Graphical abstract: Highlights: T-2 toxin induces NO generation, iNOS activity, cell apoptosis, GH deficiency. T-2 toxin induces inflammatory factors, caspase 3, 8, 9 and mitochondria damage. Excess NO results from the increase of inflammatory cytokines and iNOS activity. Mitochondria are a primary target of T-2 toxin-induced NO. NO mediates T-2 toxin-induced GH deficiency via mitochondria-dependent pathway.